Factors influencing the occurrence of infertility in pregnant women in Sriamur Village in 2023 - Sirait, Lenny Irmawaty; Triani, Annisa; Intarti, Wiwit Desi (Institute of Computer Science (IOCS), 2024)
The study conducted in Sriamur Village, Tambun Utara District in 2023 aimed to investigate factors influencing infertility among women of reproductive age (PUS). Infertility, defined as the inability to conceive after one year of unprotected intercourse or inability to carry a pregnancy to term, was examined in relation to age, lifestyle, BMI, stress, and menstrual disorders. Using quantitative cross-sectional research, the study analyzed data from 16 infertile PUS using a total sampling technique. The results indicated significant relationships between several factors and infertility. Regarding age, both husbands and wives showed no statistically significant relationship. Similarly, lifestyle, BMI, stress, and menstrual disorders exhibited no significant association with infertility among both husbands and wives. However, the study concluded that there was a relationship between age, lifestyle, BMI, stress, and menstrual disorders with the occurrence of infertility among PUS in the study area. This research contributes valuable insights into understanding the multifactorial nature of infertility and highlights the importance of addressing various aspects such as lifestyle choices, stress management, and menstrual health in the context of reproductive health. By identifying these factors, healthcare professionals can develop targeted interventions and support strategies to help individuals facing infertility in Sriamur Village and similar communities.